Pengaturan Kecepatan Motor DC dengan Kontrol Proporsional Integral Derifatif (PID) Berbasis LabView - Alifa Restu Janwar Wiriawan (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
Abstract - DC motors are widely used in small and large industries. DC motor speed is often unstable due to outside interference and changes in the parameters of the fabrication so it is necessary to design a controller. Motor DC speed adjustment and monitoring is a crucial system as it i implemented in industrial. This motor DC speed adjustment and monitoring using computer interface where in industial this system will support operator for adjusting and monitoring motor speed. For acquiring best control parameters, tuning is needed for acquiring best Proportional Integral Derivative(PID) value. This tuning is used for find the best proportional gain, time integral, derivative time. PID controller will give a better control respond to the DC Motor based on the error, the DC motor rotation speed needed is called Setpoint. The labview software used as an interface of monitor and control. Keyword : LabView, Motor DC, Arduino, Ouptocoupler, Computer